2010
DOI: 10.1103/physrevb.81.174525
|View full text |Cite
|
Sign up to set email alerts
|

Intermode dephasing in a superconducting stripline resonator

Abstract: We study superconducting stripline resonator (SSR) made of Niobium, which is integrated with a superconducting interference device (SQUID). The large nonlinear inductance of the SQUID gives rise to strong Kerr nonlinearity in the response of the SSR, which in turn results in strong coupling between different modes of the SSR. We experimentally demonstrate that such intermode coupling gives rise to dephasing of microwave photons. The dephasing rate depends periodically on the external magnetic flux applied to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…MHz, which has already exceeded the observed Kerr strength obtained by exploiting a large Josephson junction connected with the TLR in the recent papers [44][45][46].…”
Section: Coupling Between the Tlrs And The Moleculementioning
confidence: 76%
“…MHz, which has already exceeded the observed Kerr strength obtained by exploiting a large Josephson junction connected with the TLR in the recent papers [44][45][46].…”
Section: Coupling Between the Tlrs And The Moleculementioning
confidence: 76%
“…We introduce a novel method for achieving strong and tunable optomechanical coupling, which is based on positioning a metallically coated optical fiber near the mechanical resonator. The microwave cavity, which is made of a superconducting aluminum microstrip, exhibits Kerr type nonlinearity [11,22,74,85], which significantly affects the dynamics of the entire op-tomechanical system [56]. We study the dependence of the self-excited oscillations on the driving parameters of the cavity and found that a good agreement with theory can be obtained provided that cavity nonlinearity is taken into account [56].…”
mentioning
confidence: 99%
“…On the other hand, many theories and experiments involved cross-Kerr effect have been discussed in circuit QED [48][49][50][51][52][53][54][55][56][57]. Experimentally, based on the cross-Kerr nonlinearity, the observation of quantum state collapse and revival [52], the investigation of the feasibility of microwave photon counting [53], and the realization of the giant cross-Kerr effect for propagating microwaves [54] have been reported.…”
Section: Introductionmentioning
confidence: 99%